Case Study of Colon in Loop Radiography Technique in Clinical Malignant Neoplasma in The Radiology Installation of ‘Aisyiyah Ponorogo Hospital - Azizah, Nur; Mahanani, Ayu; Mufida, Widya (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
A colonoscopy in loop for malignant neoplasms in the Radiology Department of 'Aisyiyah Ponorogo General Hospital (RSU) is performed using an NGT tube and a Rieser sphygmomanometer balloon as aids, along with gradual contrast media injection without fluoroscopy. This procedure differs from the standard rectal tube with fluoroscopic monitoring. This study aims to determine the procedure for a colonoscopy in loop and analyze the rationale for using an NGT tube, a Rieser sphygmomanometer balloon, and a technique without fluoroscopy in the department. The research method used a descriptive qualitative approach with case studies through observation, interviews, and documentation of three radiographers and one radiologist. Data were analyzed through data reduction, presentation, and conclusion drawing. The results showed that the examination procedure begins with patient preparation, including a low-fiber diet, consumption of soft foods, physical activity, and fasting before the examination. The contrast medium was administered in 200 cc increments at each stage, in the following order: lateral, AP, extended AP, oblique (LPO and RPO) projections, and then a post-evacuation AP image. The final stage consisted of a double-contrast image with 5–6 pumps of air. This technique is capable of producing clear radiological images to support the diagnosis, especially in malignant neoplasms. The study's conclusions confirm that the colon in loop examination at RSU 'Aisyiyah Ponorogo differs in the use of equipment and contrast medium compared to the general theory. This modification still produces optimal images for detecting colon abnormalities, including polyps and masses.